2019
DOI: 10.1111/echo.14400
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of left atrial function in type 2 diabetes mellitus patients with nonalcoholic fatty liver disease by two‐dimensional speckle tracking echocardiography

Abstract: Objective To assess left atrial function in type 2 diabetes mellitus (T2DM) patients with nonalcoholic fatty liver disease (NAFLD) by two‐dimensional speckle tracking echocardiography (2D‐STE). Methods We classified 97 patients with T2DM into three groups according to the results of liver ultrasonography: group A (without NAFLD), group B (mild fatty liver), and group C (moderate to severe fatty liver). Conventional echocardiography parameters included left atrial end‐systolic diameter (LAD), left ventricular e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
(78 reference statements)
0
8
0
Order By: Relevance
“…Ten observational studies comprising 1800 T2DM participants, of which 1124 (62.4%) T2DM with NAFLD were included 22–31. We assessed the risk of bias in all eligible studies based on the CSSQ checklist, and all studies achieved scores of 7–9 points (see online supplemental table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Ten observational studies comprising 1800 T2DM participants, of which 1124 (62.4%) T2DM with NAFLD were included 22–31. We assessed the risk of bias in all eligible studies based on the CSSQ checklist, and all studies achieved scores of 7–9 points (see online supplemental table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the large population-based prospective CARDIA Study showed that NAFLD is longitudinally associated with subclinical LV remodeling, abnormal geometry, and impaired LV longitudinal strain after a five-year follow-up [15]. Several small studies have shown that NAFLD is associated with decreased LA strain indices [26,27]. There is a plethora of evidence that supports the adverse effects of NAFLD on diastolic function [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…A 2019 meta-analysis of 16 observational studies further confirmed that NAFLD (as detected by imaging techniques or liver biopsy) was independently associated with many functional and structural myocardial abnormalities, including higher left ventricle mass, higher left ventricular end diastolic diameter, higher left atrium diameter and the ratio between left atrial volume and body surface area, higher posterior wall and septum thickness, lower E/A wave ratio, higher E/E ratio, longer deceleration time and longer relaxation time [58]. Interestingly, recent observational studies also indicated that NAFLD (as detected by ultrasonography) was associated with a reduction in global longitudinal strain, which is a relatively novel echocardiographic parameter strongly associated with adverse cardiovascular outcomes [59][60][61]. NAFLD was associated with an increased risk of incident CKD (random-effects hazard ratio 1.43, 95% confidence interval 1.33-1.54)…”
Section: Sub-clinical Myocardial Remodelling and Dysfunction Heart Va...mentioning
confidence: 99%